Frequency response modeling of active filters - Africa, Aaron Don M. (Animo Repository, 2020)
© 2020, World Academy of Research in Science and Engineering. All rights reserved. It is expected from this paper that Active filters will be discussed in detail and strengthened with examples. There will be explanations on the different types of this filter, and also the different passes, which will show what the signal will or will not have. The concept and theory behind the filters will also be discussed, as to give a proper introduction to filters. Data concerning the differences among these types will be evidence to prove and demonstrate how the filters can affect the signal in different situations. Lastly, the paper will explain how a filter is used and how it works. The numerous applications behind filters and how they affect signals will show how important they can be to clean and remove unnecessary parts of said signal. Hence, the paper will be separated in a certain way, with the initial half explaining the general information behind it, and the second half explaining in further detail and giving some data to enhance the envision of the filter.